PENGARUH MEDIA YOUTUBE TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL DI BANDAR LAMPUNG - Azizah, Aura Khoirunnisa; Harianto, Jimi; Pamungkas, Arimbi (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
Youtube is a platform or media that people, both adults and children often use. Along with the development of technology, of course, this can affect the social-emotional development of students if it is continuously used. The role of digital media such as YouTube in shaping the mindset and behaviour of these children is a major concern for all of us, one aspect that needs to be considered is its influence on social-emotional development in Bandar Lampung. This study aims to determine the effect of using YouTube media on social-emotional development in Bandar Lampung. This study uses quantitative research methods with an inferential statistical research design, using a population and sample of 32 students. Data collection techniques using observation sheets and questionnaires. The results showed that there was an effect of t-count> t-table with a significance level of 5% or 0.05, namely 2.663> 2.042, so it can be concluded that Ho is rejected. Ha is accepted, namely there is an influence between the use of YouTube media on social-emotional development in Bandar Lampung.